Using Fillers as Women’s Language Markers in Conversation Found in Redeeming Love Movie - Nuryanti, Dewi (Anaphora : Journal of Language, Literary, and Cultural Studies, 2025)
The purpose of this research is to analyze the use of fillers in the Redeeming Love (2022) movie in terms of its types, functions, and possible causes of filler usage, especially in Angel’s speech. Fillers, often dismissed as meaningless hesitations, carry pragmatic, psychological, and sociolinguistic functions that are particularly revealing when examined through gendered communication. The research employs a descriptive qualitative method using transcription data from selected scenes in the film. The data are taken from Redeeming Love movie and are analyzed using the theory of Rose (1998), Stenström (1994), and Duvall et al. (2014). The analysis identifies both lexical and non-lexical fillers, with significant emphasis on hesitation and emotional reinforcement. The findings suggest that Angel’s use of fillers reflects internalized anxiety, social power imbalance, and identity negotiation—all of which are critical in interpreting women’s speech patterns in patriarchal narrative structures. This research contributes to a more nuanced understanding of female language features in cinematic discourse.